Analysis of whole-genome binding patterns of GAGA and CNC transcription factors during Drosophila melanogaster development - I. I. Brusentsov; D. A. Karagodin; E. M. Baricheva; T. I. Merkulova (Вавиловский журнал генетики и селекции)
On the basis of available data of ChIP-seq and ChIPchip experiments performed using antibodies against GAGA and CNC transcription factors, genome-wide binding mapping of these factors at hours 0–12 and 16–24 of Drosophila embryogenesis, as well as on white pre-pupae stage, was conducted. It was shown that the bulk of GAGA and CNC binding falls into promoter regions and introns, with the maximal density of peaks in the vicinity of the transcription start site. Moreover, in both 0–12 and 16–24 hour old embryos GAGA and CNC are frequently co-localized, while on white pre-pupae stage there is no co-localization of these factors on a genome–wide scale. In order to select a set of genes potentially co-regulated by GAGA and CNC, the study of their co-binding in annotated regulatory regions (promoter areas and segments corresponding to the 5’-UTR and 3’-UTR of mRNA) was performed. The results obtained clearly demonstrated that the sets of genes characterized by co-binding of both factors vary greatly at different stages. Thus from 353 genes with overlapped GAGA and CNC binding loci on the 0–12 hour old embryos and 611 genes on the 0–12 hour old embryos only 61 genes “belong” to both stages. For an explanation it is proposed that different sets of target genes are regulated by combinations of various GAGA and CNC isoforms, which are characterized by distinct expression patterns during drosophila embryogenesis. Functional annotation analysis of genes, in whose regulatory regions both GAGA and CNC were found at all investigated stages, demonstrates enrichment by genes controlling embryogenesis, neurogenesis and wing development. The data obtained suggest the interaction of GAGA and CNC during D. melanogaster embryogenesis.